Why are some households so poorly insured? - Gathergood, John; Wylie, Daniel (Elsevier, 2018)
e explore empirically how households insure themselves against consumption volatility. We asked households how they would fund an unexpected emergency consumption expense equivalent to one month’s income. Answers reveal a range of consumption insurance mechanisms, including borrowing from credit markets and social networks. Despite this, more than one fifth of households have no plan to insure their consumption. The likelihood of non-insurance increases with poor financial literacy and is highest among households most at risk of experiencing a financial shock. Among these households we see large effects of poor financial literacy on non-insurance.